2020
DOI: 10.3171/2020.9.focus20703
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric neurosurgery during the COVID-19 pandemic: update and recommendations from the Brazilian Society of Pediatric Neurosurgery

Abstract: OBJECTIVESCoronavirus disease (COVID-19) is a potentially severe respiratory illness that has threatened humanity globally. The pediatric neurosurgery practice differs from that of adults in that it treats children in various stages of physical and psychological development and contemplates diseases that do not exist in other areas. The aim of this study was to identify the level of knowledge and readiness of the healthcare providers, as well as to evaluate new preventive practices that have been introduced, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 18 publications
0
12
0
2
Order By: Relevance
“…O estudo foi realizado com 76 membros ativos da Sociedade Brasileira de Neurocirurgia Pediátrica (SBNPed) que responderam a um questionário online a fim de avaliar o impacto da pandemia na sua prática clínica. Este foi conduzido durante a pandemia, de março a julho de 2020 (BALLESTERO;FURLANETTI;.…”
Section: Discussionunclassified
“…O estudo foi realizado com 76 membros ativos da Sociedade Brasileira de Neurocirurgia Pediátrica (SBNPed) que responderam a um questionário online a fim de avaliar o impacto da pandemia na sua prática clínica. Este foi conduzido durante a pandemia, de março a julho de 2020 (BALLESTERO;FURLANETTI;.…”
Section: Discussionunclassified
“…According to a survey conducted by Jean et al [20], one-half of the responders reported a drop of about 50% in total operative volume. A similar study conducted by the Brazilian Society of Pediatric Neurosurgery informed that 90.7% of the neurosurgical activity was compromised and overall elective neurosurgical procedures were cancelled or postponed in 57.3% of the cases [18].…”
Section: Peculiarities Affecting Pediatric Neurosurgerymentioning
confidence: 92%
“…Chemotherapy was temporarily delayed. Overall, there was a significant decrease in the volume of pediatric cases [18,20]. According to a survey conducted by Jean et al [20], one-half of the responders reported a drop of about 50% in total operative volume.…”
Section: Peculiarities Affecting Pediatric Neurosurgerymentioning
confidence: 97%
See 2 more Smart Citations